Migration in Differentiated Localities: Changing Statuses and Ethnic Relations in a Multi‐Ethnic Locality in Transylvania, Romania. Issue 4 (9th April 2015) - Anghel, Remus Gabriel
Abstract: In recent years, an increasing number of scholars have started to analyse the effects of migration in societies of emigration. This scholarship often depicts migration as a powerful process generating 'levelled' processes of diffusion of money, goods, ideas, and values, ultimately changing entire communities and regions of origin. The paper diverges from this view and argues for a differentialist approach in researching processes of migration and social change. I substantiate this claim by analysing patterns of migration and social change in a multi‐ethnic community in Romania that consists of Hungarians, Romanians, and Roma. The research fieldwork consisted of qualitative interviews and participant observation. By using a perspective inspired by the literature on critical social capital and mechanisms of migration, I show that local social differentiation profoundly affects not only the development of migration but also the relationship between migration and social change. As I unfold in the paper, social closure based on ethnic and class/group membership had a strong effect on the ways in which Hungarians, Roma, and Romanians migrated towards Hungary, Italy, and Germany, as well as on the economic niches they occupied in countries of destination. The enrichment of some Roma and the new social position they gained reveals that migrant localities are contested social spaces where migrants' new social statuses and the ideas and values they bring back with them are weighted and negotiated against local values and systems of classification. Copyright © 2015 John Wiley & Sons, Ltd.